Intelegensi Media Teknologi Untuk Meningkatkan Kemampuan Bahasa Anak Usia Dini - Riani Agustina; Riska Yulia (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Integrating infomaation technology media in language learning can produce the latest information to improve languaage skills and mastery, especially in early chilldhood. The research method used Systematic Literature Review. Date collecation during2018-2023. The articles used in this study were 36 national and accredited jourmal articles obtained from Google scholar, Scholar, Rasearch Gate, SINTA, DOAJ. Based onthis research,it is found that the integration of technology-based mediain learming can create eariy childhood interest, attract attention, make children happier and more motivated to leam and accelerate language acquisition.